Pengaruh Jumlah Penduduk, IPM , PDRB Perkapita dan Jumlah Pengangguran terhadap Jumlah Penduduk Miskin di Kalimantan Selatan Tahun 2010 s.d. 2019 - Redhani, Faisal; Wardhana, Ali (PPJP Universitas Lambung Mangkurat, 2023)
This study aims to analyze the influence of the population number, human development index, GRDP per capita, and unemployment rate on the number of poor people in South Kalimantan from 2010 to 2019. The analytical method used in this research is Ordinary Least Square (OLS) and panel data (pooled data), which is a combination of time-series data began in 2010 to 2019 and cross-section data in the form of 13 districts/cities data in the province South Borneo. The analysis in this study was carried out with Eviews 10 software. The results in this study are the Population Variable has a positive and significant effect on the Poor Population in South Kalimantan province, the Human Development Index Variable has a negative and insignificant impact on the Poor Population in South Kalimantan Province, the GRDP Per capita Variable has a negative and little effect on the Number of Poor population in South Kalimantan province, and the Number of Unemployment Variable has a positive and significant impact on the Number of Poor Population in South Kalimantan Province.